285 THE COST OF CO-PAYS FOR AN INDIGENT ASTHMATIC POPULATION. (10th December 2015) - Stoltzfus, K. B.; Sievers, M.; Mickelsen, R.; Tollestrup, K.; Urbina, C.
Abstract : Introduction: High levels of co-payments (co-pays) have been shown to deter the use of necessary medical services and essential medications. We sought to determine the effect of an increase in pharmacy co-pay for an indigent asthmatic population on medication compliance and healthcare utilization. Methods: We performed a chart review of indigent patients 18-64 years of age enrolled in the University of New Mexico (UNM) Care program with an ICD-9 diagnosis of asthma and compared these data to prescriptions filled through the UNM Pharmacy. After a pharmacy co-payment increase for medications, we examined (1) the rate of prescribed asthma medications versus filled medications, (2) hospital admissions for treatment of an asthma exacerbation, and (3) primary physician visits for asthma-related care. Univariate and bivariate statistical analyses were performed using two-sided one sample t-tests. Results: The study originally involved 177 asthma subjects; however, fourteen subjects were excluded: two were under 18 years of age and twelve had unavailable medical charts. The number of asthma medication prescriptions filled decreased with an increase in co-pay amount (-0.49, 95% CI: 1.03 to 0.05; p= 0.07). A decrease in the number of prescriptions filled was seen in all age groups: for ages 18-34 years (change of -0.48, 95% CI: 1.96 to 1; p=0.51), for ages 35-49 years (change of -0.35, 95% CI: 1.13 to 0.43; p=0.37), for ages 49-64 years (change of -0.67, 95% CI: -1.53 to 0.19; p= 0.12). There was a greater decrease in the number of prescriptions filled by women than by men (change of -0.50, 95% CI -1.1 to 0.1; p= 0.1 compared to -0.37 95% CI -1.45 to 0.71; p=0.50 respectively). There were small increases in clinic visits (0.2, 95% CI 0.03 to 0.07; p=0.46) and hospital admissions (0.03, 95% CI -0.13 to .019; p=0.69). The sample size of 163 patients achieved 80% power to detect a difference of -0.77 and 0.77 with a standard deviation of 3.5 and a significance level of 0.05 using a two-sided one sample t-test. Conclusions: In an indigent asthmatic population after an increase in pharmacy co-pays, there was a trend within all age groups toward decreased compliance with filling asthma medications. A small difference was seen in the number of primary physician visits, and no change in the number of hospital admissions.